‘Elveland’: Irony and Laughter as Power Media in Sea Sámi Folk-Song Tradition - Fredriksen, Lill Tove (Nordlit, 2004)
The article is a literary analysis of the satirical Sámi folk-song Elveland. The song about about the road man, forester and river attendant Elveland on the west side of the municipality of Porsanger was made in the beginning of the 1900s, as a form of revenge on the part of the local community because he would not let them cut as much firewood as they needed. With irony as an important device, the text serves as a meeting point for dialogues between different voices, and where power relations and the political nature of cultural identity is revealed.